Value chain competitiveness analysis: entrepreneurial behavioural practices determining business success in Uganda's commercial sugar and forestry industries - Mugabira, Michael Imaka (Research of GSB, 2018)
Global value chain (GVC) participation has been placed on a high level policy agenda by Development Partners as a prescription template for agri-business growth and competitiveness of developing countries, especially sub-Saharan Africa. Despite, the GVC participation popularity in application, there is an intense debate questioning why some countries are advancing in the global marketplace, while others are failing to do so. Actors' (entrepreneur's) behavior has been highlighted by the value chain fraternity researchers as an area of interest to investigate this phenomenon. The purpose of this research was to contribute to the understanding of the link between the entrepreneur behavior and better enhanced competitiveness in GVC, and as such offer some key insights into the emerging GVC theory. Case Study Approach was the major research strategy complemented by the Survey. Polar types of Ugandan commercial sugarcane and forestry farmers were selected, namely high and low performing entrepreneurs. Principal unit of analysis was the entire value chain, analyzed at three levels: Micro (Farm Enterprises), Meso (Farmer/Miller) and Macro (National Policies & Regulatory Environment). Principal component analysis was run for purposes of grouping items. Empirical data was analyzed using within case analysis, and cross-case pattern analysis. Theoretically and policy practice this study has brought into insight new research frontiers: (1) The finding of internality behavior demonstrates that entrepreneur's traits, characteristics and actions are basically behaviors that can be learnt, nurtured, and developed into a business culture, competencies and capabilities for enterprise growth, productivity and competitiveness. Therefore, policy program designs should focus on igniting these behaviors which are already embedded in the minds of the entrepreneurs, and then supporting the strengthening of such behavioral changes for entrepreneurs to effectively participate in GVC in developing economies. (2) Institutional quality defined by the set of rules of the game with the associated governance power matters with respect to equitable wealth distribution and ultimately competitiveness. Findings of this study are being used to inform both the drafting of the National Sugar Bill 'Draft Uganda Sugar Act 2015' and improvement of the regulatory environment of Uganda's Forestry Industry Sector.